Phenomenological study of heavy neutrinos at the LHC using the vector boson fusion technique (2017)
"The standard model (SM) gathers the entire understanding of fundamental particles and their interactions. Although the model has successfully explained various physical phenomena observed experimentally, there are still multiple unanswered questions concerning particle physics. ... This monograph includes a review of the neutrino mass problem in the SM, the theoretical background of the Seesaw mechanism, and a summary of previous heavy neutrino search experiments. Also, this monograph includes the results of a phenomenological analysis seeking to establish whether a search of heavy neutrinos in final states with hadronically decaying tau leptons, and using the vector boson fusion technique, was feasible to be performed at the LHC.